THE MEANING OF COLOR TERM IN CHINESE AND INDONESIAN IDIOMS: NATURAL SEMANTIC METALANGUAGE APPROACH - Ayesa, Ayesa (Universitas Gunadarma, 2021)
Every human being has the same vision for colors. On the other hand, idioms –as an embodiment of the expression of human experience, can certainly be a medium for expressing the universal meaning possessed by humans across cultures, including the meaning of colors. Through the meaning of colors term in idioms, the universality of the human mind can be known. Natural Semantic Metalanguage is an approach that tries to see the universality of language. By using six-color term in the Morris Swadesh word list, this study aims to find out the universality of the meaning of colors term in Indonesian and Mandarin. This study shows the meaning of the 'black' colors term in Indonesian and Mandarin idioms is universal. Moreover, the meaning of the colors 'black', 'green' and 'red' is universal in the concept of associating colors with objects and conditions.